3508 Ciclopirox Olamine Demonstrates Inhibitory Effects on Esophageal Tumor Cells. (27th March 2019) - Ryan, Randi; Anant, Shrikant; Ramamoorthy, Prabhu; Subramaniam, Dharmalingam; Weir, Scott
Abstract : OBJECTIVES/SPECIFIC AIMS: Drug repositioning has the potential to accelerate translation of novel cancer chemotherapeutics from bench to bedside. The goal of this study was to determine the effects of ciclopirox olamine (CPX) on esophageal tumor cells. METHODS/STUDY POPULATION: We tested the effect of CPX on four esophageal cancer cell lines, assessing cell proliferation and viability by hexosaminidase and clonogenicity assay, respectively. We analyzed the effects of CPX on three-dimensional (3D) esophageal tumor cell spheroids. We also analyzed effects on cell cycle by flow cytometry. For mechanism, we performed western blots for proteins involved in cell cycle regulation, apoptosis and the Wnt/β-catenin pathway. For in vivo effects, we performed a murine xenograft model with intraperitoneal administration of CPX (100 mg/Kg body weight daily). RESULTS/ANTICIPATED RESULTS: CPX inhibited growth of all cell lines in a time and concentration-dependent manner. CPX also inhibited growth of esophageal spheroids. Cell cycle analysis demonstrated G0/G1 arrest in cells treated with CPX. Western blot analyses demonstrated decreased expression of cyclinD1, CDK4, CDK6, and transcriptionally active β-catenin, supporting the role of CPX in cell cycle inhibition and decreased β-catenin activity. Finally, treatment of nude mice with CPX significantly decreased tumor xenograft volume. DISCUSSION/SIGNIFICANCE OF IMPACT: CPX demonstrates anti-tumor properties in esophageal cancer cell lines. The current results justify further research into the mechanism of this inhibition. Additionally, given its established safety in humans, CPX is a potential candidate for repositioning as an adjunct treatment for esophageal cancer.